Aneurysms of the posterior cerebral artery in children. - Kaplan, P A; Hahn, F J (American Journal of Neuroradiology, 1984)
Intracranial aneurysms in children are very rare and differ from those in adults in several ways. Posterior cerebral artery (PCA) aneurysms are among the least common of intracranial aneurysms and little is known of their presentation and prognosis. Two cases of PCA aneurysms in children are reported, and 21 other cases of PCA aneurysms in patients 20 years of age or younger are reviewed. PCA aneurysms in children have a marked male predominance and are usually large, symptomatic, and tend to occur proximal or distal to the circle of Willis. Diagnostic computed tomography may be warranted earlier in children than in adults with similar symptoms referable to intracranial abnormalities because children are more likely to have an organic cause for such symptoms.